Data Mining Sistem Stock Opname Bahan Baku Catering Makanan Sehat Menggunakan Metode Min Max Stock - Chyntia Kesuma; Efori Buulolo; Hukendik Hutabarat (Bulletin of Information System Research, 2022)
Competition in today's business world is increasing, there are more and more innovations made by every entrepreneur to increase sales of the products they make so that they can be accepted in the market and in the community. One of them is Healthy Food Medan, a company engaged in healthy food catering. In making healthy food, it is necessary to stock up on good raw materials, so that one day the company does not lack stock of raw materials. Healthy Food Medan itself will not be separated from the so-called stock taking of raw materials. Of course, it is very interesting to be used as research material. Because of this, a computer program was created to determine the stock of raw materials so that there is no shortage of raw materials. In the application with the Min-Max method, it is expected that the user will no longer have difficulties in terms of stock of raw materials. The Min-Max method itself is a method that determines the maximum amount of inventory and minimum inventory so that there are no shortages and excess goods. Aims to avoid excess and shortage of raw materials by calculating the amount of raw material inventory